UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN MIMBA (Azadirachta Indica A. Juss) TERHADAP BAKTERI Stapylococus aureus Dan Escherichia coli - ST.NURJANAH, MUHAMMAD FAISAL; Hendriyani , Irmatika; Azemi , Nuruluni; Suryani, Ade Irma (JOURNAL OF PHARMACEUTICAL (JOP), 2025)
Background: Infectious diseases remain a health problem in developing countries, including Indonesia. Antibacterials are needed to inhibit or kill bacteria that cause infections. Neem leaves (Azadirachta indica A. Juss) are traditionally known to contain active compounds such as flavonoids, alkaloids, and tannins that have antibacterial potential. Several studies have shown that ethanol extracts of neem leaves are effective against bacteria such as Staphylococcus aureus and Escherichia coli. Objective:  The purpose of this study was to conduct phytochemical screening to determine the secondary metabolite content in mimba leaf extract and to test the antibacterial activity of 5%; 10%; 20%; 40%, and 80% ethanol extracts of mimba leaves against Staphylococcus aureus and Escherichia coli bacteria. Method:  Mimba leaves were extracted using the maceration method with 96% ethanol solvent. Antibacterial activity was tested using the well diffusion method with treatments of 5%; 10%; 20%; 40%, and 80% groups and a negative control group using DMSO. Results:  The inhibition zone diameters of Staphylococcus aureus and Escherichia coli at a concentration of 5% were 1,2 mm and 2 mm respectively, while the inhibition zone diameters at a concentration of 80% were 17,4 mm and 16 mm respectively. Cunclusion:  Concentrations of mimba leaf extract of 5%; 10%; 20%; 40%; and 80% showed antibacterial activity against Staphylococcus aureus and Escherichia coli. The higher the concentration, the larger the diameter of the inhibition zone formed